Establishing jet scaling patterns with a photon - Englert, Christoph; Plehn, Tilman; Schichtel, Peter; Schumann, Steffen (Journal of high energy physics, 2012)
Staircase and Poisson scaling are two typical patterns we observe for the exclusive number of jets at high energy hadron colliders. We examine these scaling properties for photon plus jets production at the LHC and find that this channel is well suited to study these features. We illustrate and discuss when to expect each of the two patterns, how to induce a transition through kinematic cuts, and how photons are related to heavy gauge bosons. Measurements of photon+jets production is therefore providing valuable information on exclusive jet scaling, which is going to help to eventually understand the theoretical origin of exclusive jet scaling properties in more detail.